2009
DOI: 10.1068/p6478
|View full text |Cite
|
Sign up to set email alerts
|

Amodal Completion is Not Completed Only behind the Occluder

Abstract: We investigated amodal completion with changes in two parameters: figure orientation, and the shape of the occluding and occluded figures. First, Markovich's [2002, Visual Mathematics 4(1); http://www.mi.sanu.ac.rs/vismath/fila] figure was presented in vertical, horizontal, and diagonal orientations. The results supported Markovich's finding of amodal completion by smooth continuity and symmetry. Amodal completion was also affected by orientation: symmetrical shape tended to appear when the pattern had vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The amodal completion pattern could be completed based on two different kinds of rules: straight continuity and symmetry. In the vertical condition adults completed the pattern as a hexagon based on symmetry and in the diagonal condition they completed it as a pentagon based on straight continuity (Markovich, 2002; Takashima et al., 2009). Compared with adults, our experiment showed that infants followed the rule of straight continuity and completed patterns as a pentagon in both orientations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The amodal completion pattern could be completed based on two different kinds of rules: straight continuity and symmetry. In the vertical condition adults completed the pattern as a hexagon based on symmetry and in the diagonal condition they completed it as a pentagon based on straight continuity (Markovich, 2002; Takashima et al., 2009). Compared with adults, our experiment showed that infants followed the rule of straight continuity and completed patterns as a pentagon in both orientations.…”
Section: Discussionmentioning
confidence: 99%
“…of this experiment showed that infants completed the pattern as a pentagon in both the vertical and diagonal conditions. In contrast, Markovich (2002) and Takashima et al (2009) showed that adults completed Markovich's pattern (Figure 2) as a hexagon in the vertical condition and as a pentagon in the diagonal condition. That is, orientation affected how adults completed the pattern, but not how infants did.…”
Section: Amodal Completion In Infants 107mentioning
confidence: 93%
See 3 more Smart Citations